GELIAT PEREMPUAN DESA SEPAT KABUPATEN SRAGEN GELORAKAN PROTOKOL KESEHATAN SAMPAI MANCA NEGARA - Sritami Santi Hatmini; Setyasih Harini (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
The Covid-19 pandemic is an unexpected challenge for society. Family resilience is at stake but not the responsibility of men as the head of the family alone. Women during pandemics actually have a very big role to help maintain the integrity of the family both physically, spiritually, and economically. Women get dual roles not only focusing on domestic affairs but instead out of their